Computational Models of Interoception and Body Regulation. Issue 1 (January 2021) - Petzschner, Frederike H.; Garfinkel, Sarah N.; Paulus, Martin P.; Koch, Christof; Khalsa, Sahib S.
Abstract : To survive, organisms must effectively respond to the challenge of maintaining their physiological integrity in the face of an ever-changing environment. Preserving this homeostasis critically relies on adaptive behavior. In this review, we consider recent frameworks that extend classical homeostatic control via reflex arcs to include more flexible forms of adaptive behavior that take interoceptive context, experiences, and expectations into account. Specifically, we define a landscape for computational models of interoception, body regulation, and forecasting, address these models' unique challenges in relation to translational research efforts, and discuss what they can teach us about cognition as well as physical and mental health. Highlights: The sensory-control loop can be used as a guiding principle to align different computational models of interoception and body regulation. Recent computational frameworks focus on formulating body regulation via flexible, adaptive control mechanisms that extend classical reflex arcs. The perception and regulation of interoceptive signals pose tangible and unique challenges for computational modeling. Concrete computational frameworks of brain–body interactions hold great potential for translational research. Modeling approaches could be applied to develop testable 'computational biomarkers' to support diagnostic, prognostic, or treatment efforts, particularly in individuals with symptoms originating from maladaptive brain–body interactions.